Biologic response modifiers for granulomatosis with polyangiitis (Wegener's): from promise to reality. (June 2013) - Clain, Jeremy M; Cartin-Ceba, Rodrigo; Specks, Ulrich
Advances in the treatment of granulomatosis with polyangiitis (GPA; formerly Wegener's granulomatosis) have resulted in marked improvements in patient outcomes. While severe GPA was originally described as progressive and invariably fatal, the use of immunosuppressive therapy has transformed the disease into a manageable, chronically relapsing illness. However, standard immunosuppressive therapies are associated with numerous side effects and significant treatment failures. In an effort to provide safer and more effective treatments for patients with GPA, several alternative therapies have been investigated in recent years, most notably among biologic response modifiers. The use of biologic response modifiers in GPA has had mixed results. The efficacy of rituximab in GPA is now firmly established, while inhibitors of TNF-α have not shown clear benefits. Investigations into other biologic response modifiers in GPA remain preliminary, but hold promise for a future in which the treatment of GPA achieves further improvements in outcomes with fewer side effects.